Magneto-electronic and optical properties of Si-doped graphene. (April 2019) - Shih, Po-Hsin; Do, Thi-Nga; Huang, Bor-Luan; Gumbs, Godfrey; Huang, Danhong; Lin, Ming-Fa
Abstract: The rich and unique magnetic quantization phenomena of Si-doped graphene defect systems for various concentrations and configurations are fully explored by using the generalized tight-binding model. The non-uniform bond lengths, site energies and hopping integrals, as well as a uniform perpendicular magnetic field ( B z z ˆ ) are taken into account simultaneously. The quantized Landau levels (LLs) are classified into four different groups based on the probability distributions and oscillation modes. The main characteristics of the LLs are clearly reflected in the magneto-optical selection rules which cover the dominating Δ n = | n v − n c | = 0, the coexistent Δ n = 0 and Δ n = 1, along with the specific Δ n = 1 . These rules for inter-LL excitations are attributed to the non-equivalence or equivalence of the A i and B i sublattices in a supercell. The spectral intensity can be controlled by oscillator strength using a canonical momentum (vector potential) as well as by density of states using concentration and distribution of doped Si atoms. Graphical abstract: The novel magneto-optical selection rules in graphene with Si-doped defect. Image 1